1995
DOI: 10.1021/ma00117a008
|View full text |Cite
|
Sign up to set email alerts
|

Thermolysis and Methanolysis of Poly(.beta.-hydroxybutyrate): Random Scission Assessed by Statistical Analysis of Molecular Weight Distributions

Abstract: Samples of a bacterial polyester, poly@-hydroxybutyrate), have been degraded thermally as a thin film on a thermocouple-controlled filament at 350 "C. In one series of these thermal experiments a short pyrolysis time (5 s) was used in order to ensure only partial pyrolysis, while in another series of thermal experiments the pyrolysis was allowed to proceed until all the sample had decomposed to volatiles. Samples from the same batch were also degraded in solution by methanolysis under acid conditions, while un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 9 publications
3
26
0
3
Order By: Relevance
“…Lehrle and Williams 101) have reported that under certain conditions random chain scission can not be responsible exclusively for the formation of the observed degradation products. In particular, it was shown that primary products are involved in a number of secondary reactions and isomerizations and, indeed, that tetramer is formed principally as a result of such secondary reactions 102) . The two monomer units i. e., 3-hydroxypentanoic acid (trivially known as 3-hydroxyvaleric acid or 3HV) and 3-hydroxybutyric acid (3HB) of PHBV copolymer are shown in Fig.…”
Section: Aliphatic Polyestersmentioning
confidence: 99%
“…Lehrle and Williams 101) have reported that under certain conditions random chain scission can not be responsible exclusively for the formation of the observed degradation products. In particular, it was shown that primary products are involved in a number of secondary reactions and isomerizations and, indeed, that tetramer is formed principally as a result of such secondary reactions 102) . The two monomer units i. e., 3-hydroxypentanoic acid (trivially known as 3-hydroxyvaleric acid or 3HV) and 3-hydroxybutyric acid (3HB) of PHBV copolymer are shown in Fig.…”
Section: Aliphatic Polyestersmentioning
confidence: 99%
“…Lehrle et al reported that the analytical results of partial pyrolysis of PHB showed some deviations from theoretical predictions of random scission statistics (Lehrle et al, 1994(Lehrle et al, , 1995. These deviations were probably due to reactions induced by the end groups.…”
Section: Suggestions Of Other Degradation Mechanismsmentioning
confidence: 99%
“…This is an important limitation for processing and consequently, to mechanical recycling. Therefore, there has been a great deal of interest in studying the thermal degradation behavior of PHB and other related poly(hydroxyalkanoate)s [29][30][31][32][33][34][35] . Also studies seeking to improve the thermal stability of PHB by grafting chemicals in PHB chain [33,36] , and adding polymeric additives in PHB matrix [37,38] have been developed.…”
Section: Introductionmentioning
confidence: 99%